The impact of 24 h consultant shop floor presence on emergency department performance: a natural experiment. Issue 5 (1st June 2012) - Christmas, Emma; Johnson, Ian; Locker, Thomas
Abstract : Objectives: As a result of gaps in middle-grade cover in the emergency department it became necessary for consultants to work some night shifts. This study aimed to examine the effect of this change in practice on performance. Methods: A prospective observational study was conducted. Staffing and workload variables were collected over a period of 6 months in a single district general emergency department. The outcomes assessed were process times, the proportion of patients admitted and the proportion of patients returning within 7 days. Results: Consultants worked 26 of 182 night shifts during the period studied. There were no differences in the number of patients present in the department at the start of the middle-grade or consultant night shifts. Fewer patients presented per hour during middle-grade night shifts: 3.8 patients per hour versus 4.4 patients per hour during consultant nights. Compared with middle-grade night shifts, the median waiting time was on average 19.6 min less and the median emergency department length of stay was 20.5 min less during consultant night shifts. The proportion of patients admitted from the emergency department was on average 3.9% less than during middle-grade night shifts but there was no difference in the proportion returning within 7 days. Conclusion: In this small single-site study, a consultant working nights has been shown to reduce process times and the rate of admission. It remains unclear whether such improvements would be sustained in the longer term.